Biochemical changes relevant to cardiovascular function in lead intoxicated calves - Dey, S; Swarup, D; Dwivedi, S K (The Indian Journal of Animal Sciences, 2012)
Effects of lead were evaluated on some biochemical parameters related to cardiovascular function in calves by giving lead acetate @ 5.0 mg (equivalent to 2.73 mg of lead)/kg body weight till the appearance of clinical signs of toxicity in calves. Lead exposure increased levels of serum cholesterol and triglycerides in calves from day 28 onwards. Serum sodium and potassium levels did not change significantly but concentrations of calcium decreased after lead exposure. Change in creatinine phosphokinase (CPK) level was most pronounced at the later stage of the experiment. These calves also revealed increasing concentration of lead in blood. Our findings revealed that lead affects cardiovascular system of bovine.